2023
DOI: 10.1093/plphys/kiad355
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from relatives: C4 photosynthesis enhances CO2 assimilation during the low-light phase of fluctuations

Abstract: Despite the global importance of species with C4 photosynthesis, there is a lack of consensus regarding C4 performance under fluctuating light. Contrasting hypotheses and experimental evidence suggest that C4 photosynthesis is either less or more efficient in fixing carbon under fluctuating light than the ancestral C3 form. Two main issues have been identified that may underly the lack of consensus: neglect of evolutionary distance between selected C3 and C4 species and use of contrasting fluctuating light tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
2
2
0
Order By: Relevance
“…These results strongly supported that the loss in photosynthetic carbon gain in maize mainly occurred in the first 2 min after transition from low to high light (Lee et al 2022). However, under condition of FL–10 min at 60% relative humidity, no significant difference in the loss in photosynthetic carbon gain was observed between maize and tomato (Figure 3B), which was consistent with the scheme that photosynthetic efficiency during high‐light phase is attributable to species rather than photosynthetic pathway (Arce Cubas et al 2023). Therefore, the previous conclusion that C 4 plants utilize FL less efficiently than C 3 plants should be revised according to the changing frequency of FL.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results strongly supported that the loss in photosynthetic carbon gain in maize mainly occurred in the first 2 min after transition from low to high light (Lee et al 2022). However, under condition of FL–10 min at 60% relative humidity, no significant difference in the loss in photosynthetic carbon gain was observed between maize and tomato (Figure 3B), which was consistent with the scheme that photosynthetic efficiency during high‐light phase is attributable to species rather than photosynthetic pathway (Arce Cubas et al 2023). Therefore, the previous conclusion that C 4 plants utilize FL less efficiently than C 3 plants should be revised according to the changing frequency of FL.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the changing frequency of FL is an important factor affecting sunfleck utilization efficiency in both maize and tomato. Consistently, a recent study found that photosynthetic efficiency under fluctuating light could be influenced by the fluctuation regime (Arce Cubas et al 2023).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations